Projek Bunga Berhitung pada Pembelajaran Matematika Kelas 2 di SD 1 ST. Yohanes Tomohon: Penelitian - Juliana Sumilat; Yesi Padoma; Priscilla Sinabang; Hestria Br Ginting; Elizha Maghda Bellen Nhirati Matahari; Marselino Yehezkiel Sengkey; Andreas Rantung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Classroom Action Research (CAR) aims to address the challenge that mathematics is often perceived as a difficult and abstract subject at the elementary level. For this purpose, an innovative strategy was implemented through the Counting Flower Project using the Project Based Learning (PjBL) Model with 8 second-grade students at SD 1 St. Yohanes Tomohon. The project serves as a concrete medium integrating the concept of addition up to 20 with the art of drawing flowers, where students visualize the arithmetic operation as the merging of two sets of numbers represented by two different colors on the flower petals. Quantitative results indicate the success of the intervention, marked by a class mean score reaching 79.37 and a classical completion percentage of 75%. This achievement surpassed the Minimum Completion Criteria (KKM) of 75. The use of this project-based visual media was effective in bridging the abstract conceptual understanding of addition , while simultaneously fostering the Pancasila Student Profile characteristics (Creativity, Independence, and Collaboration) in students. Although two students still required further assistance , the findings affirm the crucial role of creative visual media in enhancing student motivation and learning outcomes at the elementary education level.